1981
DOI: 10.1104/pp.67.5.999
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between Light Intensity and NaCl Salinity and Their Effects on Growth, CO2 Assimilation, and Photosynthate Conversion in Young Broad Beans

Abstract: MATERIALS AND METHODS Seedlings of Viiafaba were grown for four weeks at two different light intensities (55 and 105 watts per square meter) in a saline (50 millimlar NaCI) and nonsaline nutrient solution. NaCi salinity depressed growth and restricted protein formation, CO2 assimilation, and especially the incorporation of photosynthates into the lipid fraction. Conversion of photosynthates in leaves was much more affected by salinity than was photosynthate turnover in roots. The detrimental effect of NaCi sal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1983
1983
2014
2014

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(28 citation statements)
references
References 14 publications
2
26
0
Order By: Relevance
“…Direct effects of excess salt on various plant biochernical and structural functions which can cause reductions in P, capacity have been documented by Chimikhs & Karlander (1973), Helal & Mengel (1981, and Longstreth et al (1984).…”
Section: Discussionmentioning
confidence: 90%
“…Direct effects of excess salt on various plant biochernical and structural functions which can cause reductions in P, capacity have been documented by Chimikhs & Karlander (1973), Helal & Mengel (1981, and Longstreth et al (1984).…”
Section: Discussionmentioning
confidence: 90%
“…Salinity treatments progressively reduced photosynthesis and this was coincident with a decline in leaf chloroplast pigments (chlorophyll a, chlorophyll b and carotenoids). Other workers have concluded that salinity affected the rate of photosynthesis reflecting changes in pigment composition (Ahmed, et al, 1980;Helal and Mengel, 1981;and Berlin, et al, 1982). Photosynthetic activity decreased with increase in salinity concentrations in pure sand soil (SS) but increased with sand/hydrogel polymer (SS/HP) (v/v) (Fig.…”
Section: Pigment Contents and Photosynthetic Activitymentioning
confidence: 90%
“…The effects of salinity on photosynthetic rates appear to be extremely variable, ranging from a stimulation of COg uptake (Passera & Albuzio, 1978) to a reduction (Helal & Mengel, 1981;Malloch, Bamidele & Scott, 1985;Yeo, Caporn & Flowers, 1985;Flowers et al, 1985). This is probably because the salt is distributed unevenly among the different cell compartments and the extracellular spaces, so that average tissue salt loads do not accurately refiect salt concentrations at the sites of photosynthetic activity.…”
Section: Discussionmentioning
confidence: 99%